Determining factors in business creation by women: Systematic review based on PRISMA-2020 - Gallegos, Ada; Valencia, Jackeline; Gómez-Bayona, Ledy; Pacheco, Rutsmy Angel Manuel Gallegos; Londoño-Celis, Wilmer; Rodríguez-Correa, Paula Andrea (Edelweiss Applied Science and Technology, 2026)
This study systematically examines the determining factors influencing business creation by women through a PRISMA 2020-based literature review. The objective is to identify and integrate personal, social, cultural, economic, and political-legal dimensions shaping female entrepreneurship. A structured search was conducted in Scopus and Web of Science, resulting in 38 peer-reviewed studies that met the established eligibility criteria. The findings reveal that personal factors such as risk-taking ability, self-confidence, and resilience interact with structural conditions, including family support, gender norms, access to financing, and government support programs. Family support emerges as the most frequently cited social determinant, while access to financing and restrictive gender norms constitute the most persistent structural barriers. Government initiatives and training programs appear as key enabling mechanisms within the political-legal dimension. The review highlights the interdependence among these dimensions and demonstrates that female entrepreneurship cannot be explained through isolated variables. The study contributes a multidimensional conceptual framework that integrates internal capabilities with external structural conditions. The findings underscore the need for coordinated public policies, inclusive institutional ecosystems, and sociocultural transformation to promote sustainable and equitable female entrepreneurship.